Increased cancer risk in heavy drinkers with the alcohol dehydrogenase 1C*1 allele, possibly due to salivary acetaldehyde. Issue 6 (11th May 2004) - Visapää, J P; Götte, K; Benesova, M; Li, J; Homann, N; Conradt, C; Inoue, H; Tisch, M; Hörrmann, K; Väkeväinen, S; Salaspuro, M; Seitz, H K
Abstract : Background: Chronic ethanol consumption is associated with an increased risk of upper aerodigestive tract cancer. As acetaldehyde seems to be a carcinogenic factor associated with chronic alcohol consumption, alcoholics with the alcohol dehydrogenase (ADH) 1C*1 allele seem to be particularly at risk as this allele encodes for a rapidly ethanol metabolising enzyme leading to increased acetaldehyde levels. Recent epidemiological studies resulted in contradictory results and therefore we have investigated ADH1C genotypes in heavy alcohol consumers only. Methods: We analysed the ADH1C genotype in 107 heavy drinkers with upper aerodigestive tract cancer and in 103 age matched alcoholic controls without cancer who consumed similar amounts of alcohol. Genotyping of the ADH1C locus was performed using polymerase chain reaction based on restriction fragment length polymorphism methods on leucocyte DNA. In addition, ethanol was administered orally (0.3 g/kg body weight) to 21 healthy volunteers with the ADH1C*1, 1, ADH1C*1, 2, and ADH1C*2, 2 genotypes, and 12 volunteers with various ADH genotypes consumed ethanol ad libitum (mean 211 (29) g). Subsequently, salivary acetaldehyde concentrations were measured by gas chromatography or high performance liquid chromatography. Results: The allele frequency of the ADH1C*1 allele was found to be significantly increased in heavy drinkers with upper aerodigestive tract cancer compared with age matched alcoholic controls without cancer (61.7% v 49.0%; p = 0.011). The unadjusted and adjusted odds ratios for all cancer cases versus all alcoholic controls were 1.67 and 1.69, respectively. Healthy volunteers homozygous for the ADH1C*1 allele had higher salivary acetaldehyde concentrations following alcohol ingestion than volunteers heterozygous for ADH1C (p = 0.056) or homozygous for ADH1C*2 (p = 0.011). Conclusions: These data demonstrate that heavy drinkers homozygous for the ADH1C*1 allele have a predisposition to develop upper aerodigestive tract cancer, possibly due to elevated salivary acetaldehyde levels following alcohol consumption.